Obtstacles to Faster Growth in Transition Economies : The Mongolian Case - Black, Stabley (IMF Working Papers; Working Paper ;, 2001)
The obstacles to economic growth in Mongolia are modeled with a supply-side growth model calibrated to represent inefficient use of resources and intermediation. Progressive removal of inefficiencies over time by means of privatization of banks and industrial enterprises potentially leads to increased productivity and increased capital accumulation, raising economic growth and per capita output.